Case report: Catecholamine cardiomyopathy in children with neuroblastoma - Xu, Xiaoyan; Liu, Meiqi; Zhang, Yanmin; Wang, Jie; Lei, Xi; Wang, Juanli; Zhou, Yafei; Wang, Tao (Frontiers in Pediatrics, 2023)
Introduction Many endocrine diseases, such as neuroblastoma (NB), can be linked with acquired cardiomyopathy and heart failure. Neuroblastoma’s cardiovascular manifestations are typically hypertension, electrocardiogram (ECG) changes, and conduction disturbances. Case Presentation A 5-year-old 8-month-old girl was admitted to the hospital with ventricular hypertrophy and hypertension (HT) and heart failure. She had no previous history of HT. On color doppler echocardiography, the left atrium and left ventricle were enlarged. The left ventricular ejection fraction (EF) was as low as 40%, and the ventricular septum and left ventricular free wall were thickened. The internal diameters of both coronary arteries were widened. Abdominal computed tomography scan (CT) demonstrated an 8.7cm×7.1cm×9.5cm tumor behind the left peritoneum. In urine catecholamines analysis, free-norepinephrine (f-NE), free-dopamine (f-DA), free-normetanephrine (f-NMN), free-3-methoxytyramine (f-3MT), vanillylmandelic acid (VMA), and homovanillic acid (HVA) levels were all greater than the normal range for 24 hours except free-metanephrine (f-MN) and free-epinephrine (f-E). Based on these findings, we diagnosed her as NB complicated by catecholamine cardiomyopathy manifested by hypertrophic cardiomyopathy (HCM). Oral metoprolol, spironolactone, captopril and amlodipine furosemide, and intravenously injected sodium nitroprusside and phentolamine were employed for treating HT. After the tumor resection, the blood pressure (BP) and urinary catecholamine levels were all restored. After a follow-up of 7 months, echocardiography indicated normalization of ventricular hypertrophy and function. Conclusion This is a rare report showing catecholamine cardiomyopathy in NB children. Tumor resection leads to a return to normal of the catecholamine cardiomyopathy manifested as HCM.